Term Jihad Perspektif Wahbah al-Zuhayli dalam Tafsīr al-Munīr - Muhammad Zulfikar Nur Falah; Muhammad Arwani Rofi’i (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2024)
This research examines the term jihad from Wahbah al-Zuhayli's perspective in Tafsīr al-Munīr focusing on Al-Qur’ān Sūrah al-‘Ankabūt [29]: 69. The main background explains the problem of jihad in the modern era in dimensions of the school that reflect the interests of power with acts of radicalism and terrorism. This concept is closed, because it still uses the definition of jihad in the era of the Prophet Muhammad. who tend to prioritize physical attitude. Meanwhile, Tafsīr al-Munīr occupies the most appropriate position for taking formal objects, of course due to the theoretical and practical nature of interpreting the verses of the Qur'an. So this research formulates the problem of how the term of jihad is in the Al-Qur'an and Tafsīr al-Munīr's perspective on the term of jihad. The results of this research are divided into two conclusions. First, the term of jihad in the Koran is divided into the Makkiyah and Madaniyah periods. Jihad in the Makkiyah period emphasized self-defense through a persuasive attitude. Meanwhile, jihad in the Madaniyah period emphasized self-defense through physical behavior. Second, the internalization of faith in the oneness of God, the implications of human spiritual attitudes, and human rūḥiyyah behavior, are all concepts of jihad in the perspective of Tafsīr al-Munīr which focuses on the study of Al-Qur’ān Sūrah al-‘Ankabūt [29]: 69.